A Synthetic Hydrogel Composite with the Mechanical Behavior and Durability of Cartilage. (26th June 2020) - Yang, Feichen; Zhao, Jiacheng; Koshut, William J.; Watt, John; Riboh, Jonathan C.; Gall, Ken; Wiley, Benjamin J.
Abstract: This article reports the first hydrogel with the strength and modulus of cartilage in both tension and compression, and the first to exhibit cartilage‐equivalent tensile fatigue strength at 100 000 cycles. These properties are achieved by infiltrating a bacterial cellulose (BC) nanofiber network with a poly(vinyl alcohol) (PVA)–poly(2‐acrylamido‐2‐methyl‐1‐propanesulfonic acid sodium salt) (PAMPS) double network hydrogel. The BC provides tensile strength in a manner analogous to collagen in cartilage, while the PAMPS provides a fixed negative charge and osmotic restoring force similar to the role of aggrecan in cartilage. The hydrogel has the same aggregate modulus and permeability as cartilage, resulting in the same time‐dependent deformation under confined compression. The hydrogel is not cytotoxic, has a coefficient of friction 45% lower than cartilage, and is 4.4 times more wear‐resistant than a PVA hydrogel. The properties of this hydrogel make it an excellent candidate material for replacement of damaged cartilage. Abstract : The first hydrogel with the same strength and modulus as cartilage under tension and compression is developed by reinforcing a double network hydrogel with bacterial cellulose. Compared to cartilage, the hydrogel exhibits the same time‐dependent strain under compression, has the same tensile fatigue strength at 100 000 cycles, has a coefficient of friction 45% lower, and is more wear‐resistant.